Penyuluhan tentang Pendidikan Karakter Anak melalui Bahasa Positif terhadap Ibu-ibu PKK dan Posyandu di Desa Mandalle - Indarwati, Indarwati; Mariana, Lina; Rachman, Siswati; Yuliani, Nur Fadny; Firdaus, Ahmad; Siswanto, Adi (Window of Community Dedication Journal, 2020)
Character building is a long journey in educating children, the results may only be seen after months or even years. There is never one effective "recipe" that can answer all the problems in instilling a positive character in children. This service is carried out in the form of counseling which aims to increase awareness of using positive language by parents in communicating with their children. Thus, after participating in this counseling, parents in Mandalle Village, especially mothers, can be more assertive in educating and caring for their children. In addition, it is hoped that after the counseling activities take place, the parenting style for their children will get better so that children's character can be shaped properly and appropriately.